Evaluasi Risiko Proyek Implementasi Sistem Erp Di Usaha Kecil Dan Menengah - Cahyadi, Indra (Jurnal Teknik Industri, 2014)
Enterprise Resource planning (ERP) implementations in the context of small medium size enterprises (SMEs) in Indonesia is discussed in this paper. Because SMEs are vulnerable organisations with a shortage of resources, it is essential for SMEs to succesfully implement an ERP system and reduce the risks and costs of business process reengineering embedded in it. Based on the case studies this paper analyzes organizational risk factor in ERP project in two Indonesian SMEs. By using company-specific Risk Analysis Method and Characteristics Analysis Method, the recommendations of how to manage the risks in ERP projects have been given.